The cardiac sympathetic co-transmitter galanin reduces acetylcholine release and vagal bradycardia: implications for neural control of cardiac excitability. - Herring, N; Cranley, J; Lokale, M; Li, D; Shanks, J; Alston, E; Girard, B; Carter, E; Parsons, R; Habecker, B; Paterson, D (Elsevier, 2012)
The autonomic phenotype of congestive cardiac failure is characterised by high sympathetic drive and impaired vagal tone, which are independent predictors of mortality. We hypothesize that impaired bradycardia to peripheral vagal stimulation following high-level sympathetic drive is due to sympatho-vagal crosstalk by the adrenergic co-transmitters galanin and neuropeptide-Y (NPY). Moreover we hypothesize that galanin acts similarly to NPY by reducing vagal acetylcholine release via a receptor mediated, protein kinase-dependent pathway. Prolonged right stellate ganglion stimulation (10 Hz, 2 min, in the presence of 10 μM metoprolol) in an isolated guinea pig atrial preparation with dual autonomic innervation leads to a significant (p<0.05) reduction in the magnitude of vagal bradycardia (5 Hz) maintained over the subsequent 20 min (n=6). Immunohistochemistry demonstrated the presence of galanin in a small number of tyrosine hydroxylase positive neurons from freshly dissected stellate ganglion tissue sections. Following 3 days of tissue culture however, most stellate neurons expressed galanin. Stellate stimulation caused the release of low levels of galanin and significantly higher levels of NPY into the surrounding perfusate (n=6, using ELISA). The reduction in vagal bradycardia post sympathetic stimulation was partially reversed by the galanin receptor antagonist M40 after 10 min (1 μM, n=5), and completely reversed with the NPY Y(2) receptor antagonist BIIE 0246 at all time points (1 μM, n=6). Exogenous galanin (n=6, 50-500 nM) also reduced the heart rate response to vagal stimulation but had no effect on the response to carbamylcholine that produced similar degrees of bradycardia (n=6). Galanin (500 nM) also significantly attenuated the release of (3)H-acetylcholine from isolated atria during field stimulation (5 Hz, n=5). The effect of galanin on vagal bradycardia could be abolished by the galanin receptor antagonist M40 (n=5). Importantly the GalR(1) receptor was immunofluorescently co-localised with choline acetyl-transferase containing neurons at the sinoatrial node. The protein kinase C inhibitor calphostin (100 nM, n=6) abolished the effect of galanin on vagal bradycardia whilst the protein kinase A inhibitor H89 (500 nM, n=6) had no effect. These results demonstrate that prolonged sympathetic activation releases the slowly diffusing adrenergic co-transmitter galanin in addition to NPY, and that this contributes to the attenuation in vagal bradycardia via a reduction in acetylcholine release. This effect is mediated by GalR(1) receptors on vagal neurons coupled to protein kinase C dependent signalling pathways. The role of galanin may become more important following an acute injury response where galanin expression is increased.